MR2938 relieves DSS-induced colitis in mice through inhibiting NF-κB signaling and improving epithelial barrier - Ling Lv; Mireguli Maimaitiming; Shuli Xia; Jichen Yang; Tiantian Zhang; Yuming Wang; Xin Li; Iryna Pinchuk; Pingyuan Wang; Chang-Yun Wang; Zhiqing Liu (Marine Life Science & Technology, 2025)
Damage to the epithelial barrier is among key processes contributing to initiation and chronic inflammation in inflammatory bowel diseases (IBD). Only management therapy exists for IBD (e.g., anti-inflammatory and immunomodulatory agents, JAK/STAT inhibitors), and while novel therapeutic approaches have shown great potential, issues remain including route of administration, development of resistance to therapy and toxicity. Thus, novel small molecule inhibitors which can alleviate colonic inflammation and restore intestinal barrier functions are needed. Our previous study identified a new quinazolinone derivative MR2938, inspired by marine natural product penipanoid C, displaying impressive anti-inflammatory effects. In vivo efficacy study indicated that MR2938 had a dose-dependent effect on improving colitis symptoms, gut-barrier disruption, and colonic inflammation in an acute dextran sulfate sodium (DSS)-induced murine colitis as a model of epithelial injury relevant to IBD. Evaluation of potential mechanism involved in MR2938 efficacy demonstrated that MR2938 inhibited NF-κB-mediated inflammatory responses, and attenuated intestinal epithelial tight junction damage by restoring the expression of Occludin and ZO-1. Taken together, these data suggest that MR2938 is a promising lead compound for the treatment of IBD.